Sun Power Implementation for Public Parking Area in Perum Villa Mutiara Serpong, Tangerang Selatan, Banten - Nur Qosim, Muchamad; Pujotomo, Isworo; Hasanah, Aas Wasri; Hariyati, Rinna (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2021)
The existence of street lighting and / or public facilities is very important for the convenience of residents, especially in the car park at night. However, not all of them have installed lighting as in the land area, block B / C, stage 1, Villa Mutiara Serpong, Pondok Jagung, South Tangerang. This area is a land of public facilities whose area is still ground, and most of them have not installed lights to illuminate the entire area, because car parks also need lighting that is important enough to monitor unwanted things, therefore it is necessary to install the lighting of these public facilities and the road inside. this is in the form of solar powered lamps as an effective alternative for solutions in lighting and reducing the cost of using electricity from PLN. Solar lights are installed at strategic points, namely in areas with little lighting. The lamp used is a 60-90 watt power lamp for better lighting. In addition to street lighting and public facilities, an economic analysis is also carried out in this activity by comparing the total costs required between incandescent lighting and solar power. Where it is found that the nominal difference in rupiah is Rp.2,607,455, which is more efficient than incandescent PJU, and solar lamps are not affected by TDL (basic electricity cost).